WATER FOR ALL? DEVELOPING A HUMAN RIGHT TO WATER IN NATIONAL AND INTERNATIONAL LAW. Issue 4 (17th October 2016) - Arden, The Rt Hon Lady Justice
Abstract : Human rights are one of the great ideas of the twentieth century. After World War II, first Eleanor Roosevelt in relation to the Universal Declaration of Human Rights ('the Universal Declaration'), and then later the drafters of the European Convention on Human Rights ('the European Convention') saw human rights as the way to make the world fairer and safer.